EFFECTS OF PHYSICAL EDUCATION LEARNING MANAGEMENT USING ACTIVE LEARNING ON LEARNING ACHIEVEMENT IN FUNDAMENTAL MOVEMENT SKILLS ON PRIMARY SCHOOL STUDENTS - Sawangwong, Amawasri; Tingsabhat, Suthana; Suddee, Nuttaporn (Academic Journal of Thailand National Sports University, 2022)
The purposes of this research was 1) to compare the average of physical education achievement scores on fundamental movement skill before and after experiment group received active learning, 2) to compare the average of physical education achievement scores on fundamental movement skills of students between the experimental group and the control group after finishing the program. Methods: The samples consisted of 54 grade one students, obtained by simple random sampling. They were divided into 27 students for the experiment, a group who received the Active Learning in physical education management program and 27 students of the control group were assigned to study with the conventional teaching method. The research instruments were the 8 active learning lesson plans with IOC 0.77 - 0.88 and physical education achievement measurement in knowledge, attitude and fundamental movement skill measurement test with IOC 0.83, 0.97 and 1.00. and reliability in knowledge, the alpha coefficient of which was 0.784, attitude, the alpha coefficient of which was 0.790 and fundamental movement skill, the alpha coefficient of which was 0.573. The data were analyzed by mean, standard deviation and t - test. Results: 1) The mean scores of the average of physical education achievement scores on knowledge, attitude and fundamental movement skill of the experimental group were significantly higher than that before learning at a .05 level 2) The mean scores of physical education achievement measurement in attitude of the experimental group were significantly higher than that of the control group at a .05 level. The mean scores of knowledge and fundamental movement skill in the experimental group and the control group were no significant differences at a .05 level.